Terapan Metode Least Significant Bit untuk Deteksi Keaslian e-Sertifikat - Primawati, Alusyanti; Paramita, Aulia; Muchbarak, Akbar; Sulistyohati, Aprilia (LPPM, 2023)
The ease of accessing digital information allows a person to change or manipulate the data contained in the information. Therefore, the security of information or vital data from intruders or unauthorized access is important. One of the cases that are currently happening is the distribution and falsification of information through fake e-certificates. The purpose of this study is to improve security, and check the authenticity and validity of data on e-certificates using steganography techniques with the Least Significant Bit (LSB) method. Steganography is used to disguise confidential information in digital media so that confidential information is difficult to detect by unauthorized parties. The image on the certificate in the form of a pdf file will be inserted with information to validate whether the certificate is genuine or not, by reading the pixels in the image in the file. In this study, the data to be inserted is in the form of a checksum value in the form of 32 hexadecimal characters and also e-certificate information in the form of a JSON string. The results of this study are a website-based application that is capable of checking the authenticity of e-certificates.